2015
DOI: 10.1371/journal.pone.0136960
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Arabidopsis Plants Expressing Tomato Glutathione S-Transferase Showed Enhanced Resistance to Salt and Drought Stress

Abstract: Although glutathione S-transferases (GST, EC 2.5.1.18) are involved in response to abiotic stress, limited information is available regarding gene function in tomato. In this study, a GST gene from tomato, designated LeGSTU2, was cloned and functionally characterized. Expression profile analysis results showed that it was expressed in roots and flowers, and the transcription was induced by salt, osmotic, and heat stress. The gene was then introduced to Arabidopsis by Agrobacterium tumefaciens-mediated transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 38 publications
3
78
0
1
Order By: Relevance
“…Glutathione S-transferases (GSTs) are known as a family of well-characterized detoxification enzymes implicated in stress tolerance. Up-accumulation of GSTs in transgenic studies in rice (Takesawa et al, 2002) and tomato (Xu et al, 2015b) exhibited increased capability to harsh conditions such as low temperature, salt stress and drought. Our proteomic results showed that seven out of nine GSTs were found to be significantly up-accumulated by salt treatment, implying their significant roles in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) are known as a family of well-characterized detoxification enzymes implicated in stress tolerance. Up-accumulation of GSTs in transgenic studies in rice (Takesawa et al, 2002) and tomato (Xu et al, 2015b) exhibited increased capability to harsh conditions such as low temperature, salt stress and drought. Our proteomic results showed that seven out of nine GSTs were found to be significantly up-accumulated by salt treatment, implying their significant roles in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…GPX catalyzes the reduction of H 2 O 2 using Trx [150], and GST catalyzes conjugation reactions between GSH and a number of xenobiotics, playing a crucial role in the degradation of toxic substances. Previous studies have reported that overexpression of the GST gene enhanced drought tolerance in tobacco [151,152] and Arabidopsis [153]. Similarly, overexpression of P .…”
Section: Reactive Oxygen Species (Ros) Scavenging Pathwaysmentioning
confidence: 92%
“…The treatments may have primed the plants for increased tolerance as the non-stressed plants displayed elevated expression of GSTU3 when compared to the other treatments. The glutathione S-transferase enzymes play an important role in plant stress resistance as they facilitate the binding of GSH to xenobiotic substrates [35] [36]. Transgenic expression of a tomato GST, LeGSTU2, resulted in enhanced drought stress tolerance in Arabidopsis [36].…”
Section: Effects Of 17β-estradiol Application On Stress-related Gene mentioning
confidence: 99%
“…The glutathione S-transferase enzymes play an important role in plant stress resistance as they facilitate the binding of GSH to xenobiotic substrates [35] [36]. Transgenic expression of a tomato GST, LeGSTU2, resulted in enhanced drought stress tolerance in Arabidopsis [36]. GSTU3 displays increased expression in response to abiotic stress conditions [37].…”
Section: Effects Of 17β-estradiol Application On Stress-related Gene mentioning
confidence: 99%